Pengaruh Kompensasi terhadap Kinerja Pegawai Melalui Kepuasan Kerja di Puskesmas Pucang Sewu Surabaya - Yuly Sartikaningwati, Ira; Tri Wijayati, Dewie; Kristyanto, Anang (Seminar Nasional Manajemen, 2024)
The purpose of this study was to determine the effect of compensation on job satisfaction at Pucang Sewu Health Center Surabaya, to determine the effect of job satisfaction on employee performance at Pucang Sewu Health Center Surabaya and to determine the effect of compensation on employee performance through job satisfaction at Pucang Sewu Health Center SurabayaThe population in this study were 45 employees at Pucang Sewu Health Center Surabaya, with a sampling technique using a census, so the number of samples was 45 employees. The data used in this study were analyzed using the Partial Least Square (PLS) approach with the help of the smart PLS 3.0 analysis tool. The conclusion of this study is that Compensation has a significant positive effect on employee performance. Job satisfaction has a significant positive effect on employee performance and Compensation has a significant effect on employee performance through job satisfaction as a mediator.